Sensory processing sensitivity and social pain: a hypothesis and theory - Morellini, Lucia; Izzo, Alessia; Celeghin, Alessia; Palermo, Sara; Morese, Rosalba (Frontiers in Human Neuroscience, 2023)
Sensory-processing sensitivity (SPS) defined, as a personality trait, seems to be characterized by emotional sensitivity, and stronger reactivity to both external and internal stimuli. SPS can represent a risk factor for developing clinical conditions during childhood and adolescence. This personality trait is not to be considered a pathological clinical condition, however, can expose to greater environmental vulnerability. In particular, the recent studies about SPS can be contextualized to social situations that evoke traumatic and stressful emotional responses such as social exclusion. We hypothesize that Highly Sensitive People (HSP) are more vulnerable to social exclusion and social pain. This hypothesis could help structure new educational and intervention models designed to improve coping strategies and promote HSP’s psychophysical and social well-being.